2007
DOI: 10.1074/jbc.m611763200
|View full text |Cite
|
Sign up to set email alerts
|

Squalene Synthase, a Determinant of Raft-associated Cholesterol and Modulator of Cancer Cell Proliferation

Abstract: Several cues for cell proliferation, migration, and survival are transmitted through lipid rafts, membrane microdomains enriched in sphingolipids and cholesterol. Cells obtain cholesterol from the circulation but can also synthesize cholesterol de novo through the mevalonate/isoprenoid pathway. This pathway, however, has several branches and also produces non-sterol isoprenoids. Squalene synthase (SQS) is the enzyme that determines the switch toward sterol biosynthesis. Here we demonstrate that in prostate can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
0
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 46 publications
5
70
0
8
Order By: Relevance
“…16 In the present study, we confirmed that FDFT1 expression levels were significantly reduced after 6 months of androgen deprivation therapy in human prostate specimens. Further studies are warranted to confirm the androgen dependency of squalene synthase in the human prostate gland.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…16 In the present study, we confirmed that FDFT1 expression levels were significantly reduced after 6 months of androgen deprivation therapy in human prostate specimens. Further studies are warranted to confirm the androgen dependency of squalene synthase in the human prostate gland.…”
Section: Discussionsupporting
confidence: 85%
“…15 A previous study showed that FDFT1 is expressed in human prostate cancer cells, that is, LNCaP cells. 16 We also reported FDFT1 expression in PC-3 and LNCaP cells. 17 To our knowledge, the association between FDFT1 genetic polymorphisms and prostate cancer has not been studied.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…De novo cholesterol synthesis is also shown to be elevated in cancer cells (10). Cholesterol is reported to be required for the growth of cancer cells (10,15). In addition, FPP can also be converted into geranylgeranyl pyrophosphate (GGPP; ref.…”
Section: Introductionmentioning
confidence: 99%
“…ACLY converts citrate into acetyl-CoA, a precursor for fatty acid and mevalonate synthesis pathways (6)(7)(8). Both of these pathways are associated with cancer cell growth and transformation (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%